2022
DOI: 10.1186/s12873-022-00689-3
|View full text |Cite
|
Sign up to set email alerts
|

Time to recovery and its predictors among critically ill patients on mechanical ventilation from intensive care unit in Ethiopia: a retrospective follow up study

Abstract: Introduction For critically ill patients, mechanical ventilation is considered a pillar of respiratory life support. The mortality of victims in intensive care units is high in resource-constrained Sub-Saharan African countries. The recovery and prognosis of mechanically ventilated victims are unknown, according to evidence. The goal of the study was to see how long critically ill patients on mechanical ventilation survived. Methods A retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…The present study found that the overall IDR of recovery was 6.53 per 100-day observation at a 95% CI (5.67-7.50). This finding is higher than the study conducted among mechanically ventilated patients in the ICU in Dessie, Ethiopia, which found a recovery rate of 4.49 per 100 person-days with a median recovery time of 15 days (8). The possible explanation for this discrepancy may be related to the difference in the study population between our study and the Dessie study, which included both traumatic and non-traumatic patients who were mechanically ventilated in the ICU.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…The present study found that the overall IDR of recovery was 6.53 per 100-day observation at a 95% CI (5.67-7.50). This finding is higher than the study conducted among mechanically ventilated patients in the ICU in Dessie, Ethiopia, which found a recovery rate of 4.49 per 100 person-days with a median recovery time of 15 days (8). The possible explanation for this discrepancy may be related to the difference in the study population between our study and the Dessie study, which included both traumatic and non-traumatic patients who were mechanically ventilated in the ICU.…”
Section: Discussioncontrasting
confidence: 76%
“…This study found that the median recovery time of the study participants during the follow-up period was 10 days with a 95% CI (8)(9)(10)(11) and an overall recovery rate of 49.9% at a 95% CI (45.0-54.8). This result is consistent with the study conducted in South Africa, which reported that the median time to recover was 10 days (23).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…VAP is seen in a range of 9% to 24% of patients who have intubation for a duration beyond 48 hours [3]. This condition is linked to substantial morbidity and death rates, and it also results in a notable escalation in the utilization of resources [4,5]. The determination of whether a patient requires MV is contingent upon several factors, including the presence of comorbidities, the clinical condition of the patient, and the duration of MV [6,7].…”
Section: Introductionmentioning
confidence: 99%